2018
DOI: 10.1002/pc.24916
|View full text |Cite
|
Sign up to set email alerts
|

Durable, efficient, and flexible piezoelectric nanogenerator from electrospun PANi/HNT/PVDF blend nanocomposite

Abstract: Currently, there is considerable research focus on portable, lightweight, shock‐resistant, and inexpensive wearable devices that are ideally powered by harvesting abundant mechanical or vibration energy, making battery or related wiring superfluous. In this study, piezoelectric nanogenerator was electrospun from PANi (polyaniline)/HNT (halloysite nanotube)/PVDF (poly[vinylidene fluoride]) blend nanocomposite. Polymorphism, crystallinity and morphology of the nanogenerator were explored in detail. HNT and PANi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 85 publications
3
31
1
Order By: Relevance
“…The authors investigated the effect of PANi/HNT/PVDF nanocomposite on the piezoelectricity of obtained films [ 125 ], where HNT and PANi performed the roles of nucleating agent and conductive filler, respectively. The obtained output voltage was 7.2 V with a maximum current and power density of 0.75 μA and 0.25 μW/cm 2 , respectively.…”
Section: Additives To Improve Piezoelectric Properties Of Electrosmentioning
confidence: 99%
“…The authors investigated the effect of PANi/HNT/PVDF nanocomposite on the piezoelectricity of obtained films [ 125 ], where HNT and PANi performed the roles of nucleating agent and conductive filler, respectively. The obtained output voltage was 7.2 V with a maximum current and power density of 0.75 μA and 0.25 μW/cm 2 , respectively.…”
Section: Additives To Improve Piezoelectric Properties Of Electrosmentioning
confidence: 99%
“…Hence, the PNG displayed a peak open circuit voltage of 18 V, short circuit current of 1.05 mA and a peak power density of ;28 Wm -3 (Figure 24(b)). Khalifa et al (2019) introduced a blend composite to enhance the piezoelectric properties. The blend composite consists of electrospun PANi (polyaniline)/HNT (halloysite nanotube)/ PVDF.…”
Section: Flexible Pvdf Nanogeneratorsmentioning
confidence: 99%
“…Alongside, the hydrogen bonding between hydroxyl groups of HNT and the fluorine atoms of PVDF enhances the formation of β-phase [69]. Khalifa et al [70] incorporated HNT into PVDF and reported that HNT aligned themselves along the fiber axis and the produced nanofibers were fine, smooth, uniform and the mean fiber diameter decreased drastically with the incorporation of HNT.…”
Section: Nanoclaymentioning
confidence: 99%
“… Various solvent systems used for PVDF-based PEMs and fraction of β-phase obtained [ 18 , 27 , 30 , 42 , 46 , 49 , 70 , 78 , 79 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. …”
Section: Figurementioning
confidence: 99%